Reliability assessment for pipelines corroded by longitudinally aligned defects - Hosseinzadeh, Soheyl; Bahaari, Mohammad Reza; Abyani, Mohsen (Ocean engineering, 2024)
Internal corrosion poses a significant threat to offshore pipeline services. Toward offshore pipeline integrity management, this paper aims to use Finite Element Method (FEM) to assess the reliability of corroded pipelines. The FEM analysis was conducted using ABAQUS software, facilitated through Python scripts, to optimize the modeling process on a large scale. Additionally, the input database was generated through a random sampling method using the Latin Hypercube Sampling (LHS) method. The reliability of 32” oil and gas offshore internally corroded pipelines has been evaluated by fragility curve assessment along with Incremental Pressure Analysis (IPA) which is a new method inspired by Incremental Dynamic Analysis (IDA). Multiple corrosion defects pose a higher risk to offshore pipelines during service, with potentially more severe consequences than a single defect alone. Therefore, the interaction of corrosion defects has been considered in this study. Following the reliability assessment the most appropriate Probability Density Function (PDF) for the Maximum Von Mises Stress (MVMS) and failure probability at various Internal Pressure (IP) and longitudinal spacing (Sl) levels has been evaluated. •Decreasing defect spacing increases defects interaction, significantly raising MVMS and affecting reliability.•AIC and BIC tests show MVMS follows a lognormal distribution across different spacing levels against IP.•Reliability assessments show lognormal distribution fits Failure Probability across IP levels (verified by AD test).Backspa•Failure fragility curves indicate reducing spacing raises failure probability (e.g., from 35% to 75% when IP=23).•Interaction limit study reveals existing rules are conservative; over 50% show same failure pressure when spacing>0.6Dt.